To solve the quadratic equation \(x^2 - 22x + 1 = 15\) by completing the square, we first rearrange the equation:
\[ x^2 - 22x + 1 - 15 = 0 \]
This simplifies to:
\[ x^2 - 22x - 14 = 0 \]
Next, we need to complete the square for the quadratic expression \(x^2 - 22x\).
- Take half of the coefficient of \(x\), which is \(-22\), and square it:
\[ \left(\frac{-22}{2}\right)^2 = (-11)^2 = 121 \]
- Add and subtract this square inside the equation:
\[ x^2 - 22x + 121 - 121 - 14 = 0 \]
This can be rewritten as:
\[ (x - 11)^2 - 135 = 0 \]
- Now, isolate the perfect square:
\[ (x - 11)^2 = 135 \]
- Take the square root of both sides:
\[ x - 11 = \pm \sqrt{135} \]
- Finally, add 11 to both sides:
\[ x = 11 \pm \sqrt{135} \]
Thus, the solutions are:
\[ x = 11 + \sqrt{135} \quad \text{and} \quad x = 11 - \sqrt{135} \]
Now we can simplify \(\sqrt{135}\):
\[ \sqrt{135} = \sqrt{9 \cdot 15} = 3\sqrt{15} \]
So, the final answers are:
\[ x = 11 + 3\sqrt{15} \quad \text{and} \quad x = 11 - 3\sqrt{15} \]
Therefore, the correct response is:
x = 11 + 3√15, 11 - 3√15.